Understanding Simulation and Simulacra in Samsung Commercial as Powerful Public Relations Strategy - Murti, Ghanesya Hari; Samsudin, Asep (Journal of English in Academic and Professional Communication, 2019)
The aim of this study was to examine whether the students of Jember State Polytechnic could understand the embedded meaning in the Samsung mobile phone commercial as they were in taking the public relation class. This study uses purposive sampling of 30 students to determine whether they understand the work of simulation and simulacra in the commercial to provoke the customer into buying the product. The students were given the basic theory of semiotics in the initial meeting to understand the power of governing crowds using symbol in order to justify their reasoning into the image being displayed in the mobile phone commercial. This study concludes that most of students agree to buy the products without concerning the utilities but more into making a social statement when buying. The images of having high social status, being the part of global community are the significance being attached not only to the product but to customer possessing the Samsung mobile phone.Â Keywords: public relation, semiotics, Samsung, simulation and simulacra